Reclaiming Patriotism in an Age of Extremes. - Smith, Steven B. (New Haven : Yale University Press, 2021)
A rediscovery of patriotism as a virtue in line with the core values of democracy in an extremist age.
Cover -- Half Title -- Title -- Copyright -- Dedication -- Contents -- Preface -- Introduction -- ONE. Patriotism and Loyalty -- TWO. Patriotism and Its Critics -- THREE. Patriotism, Ancient and Modern -- FOUR. Nationalism and Cosmopolitanism -- FIVE. Enlightened Patriotism -- SIX. Reclaiming Patriotism -- Notes -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- X -- Y -- Z.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Citizenship-United States; Patriotism-United States; Political science-Philosophy.; Electronic books